Nano structure including dielectric particle supporter - KIM, JUN-HYUNG (2015)
Provided are a nano structure, a fabrication method thereof, and an application device using the same. The nano structure includes a substrate; a dielectric particle supporter having a surface, wherein the dielectric particle supporter is formed over the substrate, and a linker bonded to the surface of the dielectric particle supporter; and a metallic nanoparticle bonded to the linker.